Influence of EEG References on N170 Component in Human Facial Recognition - Wang, Yi; Huang, Hua; Yang, Hao; Xu, Jian; Mo, Site; Lai, Hongyu; Wu, Ting; Zhang, Junpeng (Frontiers in Neuroscience, 2019)
The choice of the reference electrode scheme is an important step in event-related potential (ERP) analysis. In order to explore the optimal electroencephalogram reference electrode scheme for the ERP signal related to facial recognition, we investigated the influence of average reference (AR), mean mastoid reference (MM) and Reference Electrode Standardization Technique (REST) on the N170 component via statistical analysis, statistical parametric scalp mappings (SPSM) and source analysis. The statistical results showed that the choice of reference electrode scheme has little effect on N170 latency (p>0.05), but has a greater impact on N170 amplitude (p<0.05). ANOVA results show that, for the three references scheme, there was statistically significant difference between N170 latency and amplitude induced by the unfamiliar face and that induced by the scrambled face (p<0.05). Specifically, the SPSM results show an anterior and a temporo-occipital distribution for AR and REST, with just anterior distribution shown for MM. However, the circumstantial evidence provided by source analysis is more consistent with SPSM of AR and REST. These results indicate that the experimental results under the AR and REST references are more objective and appropriate. Thus, it is more appropriate to use AR and REST reference scheme settings in future facial recognition experiments.